2016
DOI: 10.1371/journal.ppat.1005610
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein Receptors Redundantly Participate in Entry of Hepatitis C Virus

Abstract: Scavenger receptor class B type 1 (SR-B1) and low-density lipoprotein receptor (LDLR) are known to be involved in entry of hepatitis C virus (HCV), but their precise roles and their interplay are not fully understood. In this study, deficiency of both SR-B1 and LDLR in Huh7 cells was shown to impair the entry of HCV more strongly than deficiency of either SR-B1 or LDLR alone. In addition, exogenous expression of not only SR-B1 and LDLR but also very low-density lipoprotein receptor (VLDLR) rescued HCV entry in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
95
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 68 publications
7
95
0
Order By: Relevance
“…[33][34][35] Apo-A1-CD63 presenting exosomes produced by 293T cells were loaded with miR-26a by electroporation and shown to be internalized by HepG2 cells via SR-B1 receptor-mediated endocytosis. The exosome-mediated delivery of miR-26a to HepG2 cells was further shown to upregulate miR-26a expression, where it downregulated key cell cycle proteins that arrested the cell cycle and inhibited cell proliferation.…”
mentioning
confidence: 99%
“…[33][34][35] Apo-A1-CD63 presenting exosomes produced by 293T cells were loaded with miR-26a by electroporation and shown to be internalized by HepG2 cells via SR-B1 receptor-mediated endocytosis. The exosome-mediated delivery of miR-26a to HepG2 cells was further shown to upregulate miR-26a expression, where it downregulated key cell cycle proteins that arrested the cell cycle and inhibited cell proliferation.…”
mentioning
confidence: 99%
“…HCV cell-free transmission starts from engagement of cell-free virions with several entry receptors (13,14), including scavenger receptor class B type I (SRBI) (15), the tetraspanin CD81 (16), the tight junction proteins claudin-1 (CLDN1) (17) and occludin (OCLN) (18), and the receptor tyrosine kinases epidermal growth factor receptor (EGFR) (19), Niemann-Pick C1-like 1 cholesterol absorption receptor (NPC1L1) (20), syndecan 1 (SDC1) (21), and other lipoprotein receptors (22). After internalization, membrane fusion between viral and endosomal membranes induced by low pH leads to release of capsid in the cytosol.…”
mentioning
confidence: 99%
“…In addition, in the same study it has been demonstrated that SR‐B1, LDLR, NPC1L1 and CLDN1 were not directly involved in VLDLR‐mediated HCV infection and that VLDLR‐mediated HCV entry required HCV E2 and apoE. Recently, it has been observed that exogenous expression of SR‐B1, LDLR and VLDLR rescued HCV entry in the SR‐B1 and LDLR double‐knockout cells, confirming that VLDLR has a role in HCV entry 8.…”
Section: Hcv Interaction With Lipid and Lipoprotein Metabolismmentioning
confidence: 84%
“…Also, lipoprotein receptor‐mediated HCV entry has been found to be dependent on the density of the LVPs 8. Finally, Boyer et al .…”
Section: Hcv Interaction With Lipid and Lipoprotein Metabolismmentioning
confidence: 98%
See 1 more Smart Citation